THE EFFECT OF THE APPLICATION OF THE GUIDED INQUIRY MODEL WITH THE PROBLEM SOLVING APPROACH ON STUDENTS 'OBSERVATION SKILLS IN ADDITIVE AND ADDICTIVE MATERIALS - Ulwan Hibattul Wafi; Syaiful Arif (INSECTA: Integrative Science Education and Teaching Activity Journal, 2020)
Science learning requires an active role from students, but in general students are taught about the concept of science learning with the teacher as the center (teacher center). The impact is the lack of the role of students in understanding science which should emphasize the active participation of these students. The student should have the observation skills to learn science by maximizing the five senses. Observation skills if they are already proficient, then the initial efforts of students to have Science Process Skills have been fulfilled. This study aims to determine the effect of implementing the guided inquiry model with a problem solving approach on students' observation skills on additive and addictive substances in class VIII SMPN 1 Sambit Ponorogo in the 2019/2020 academic year.